GE_GERICHTE C/26912/2009 vom 27. Oktober 2014 - GE Cour de justice (2014)
BAIL À LOYER; ANNULABILITÉ; RÉSILIATION; PRINCIPE DE LA BONNE FOI; SOMMATION | CPC.317.1; CO.271a.1; CO.271a.1.D; CO.271a.3; CO.257f.3